Infant, maternal, and familial predictors and correlates of regulatory problems in early infancy: The differential role of infant temperament and maternal anxiety and depression. (December 2017) - Martini, Julia; Petzoldt, Johanna; Knappe, Susanne; Garthus-Niegel, Susan; Asselmann, Eva; Wittchen, Hans-Ulrich
Abstract: Abstract background: Excessive infant crying, feeding and sleeping problems are likely to emerge from the complex interplay of various factors. Aims: To investigate the role of infant (e.g., temperament), maternal (e.g., anxiety and depressive disorders), and familial (e.g., social support) factors as potential precursors of infant regulatory problems. Study Design: Prospective-longitudinal study. Subjects: 286 mother-infant dyads were investigated from early pregnancy until 16 months postpartum via questionnaires and interviews. Outcome measures: Regulatory problems at 2, 4 and 16 months postpartum assessed by standardized diagnostic interviews. Results: Fussy infant temperament and maternal anxiety disorders were associated with excessive infant crying (OR=1.16, 95%CI:1.05-1.29, OR=3.28, 95%CI:1.16-9.26) and feeding problems (OR=1.05, 95%CI:1.01-1.11, OR=2.27, 95%CI:1.36-3.80) whereas maternal depressive disorders were associated with infant sleeping problems (OR=2.55, 95%CI:1.06-6.11). Moreover, high maternal age (OR=0.86, 95%CI:0.75-0.98) was associated with a lower risk for excessive crying and being a single mother (OR=0.16, 95%CI:0.03-0.73) and cognitive reappraisal to regulate emotions (OR: 0.59, 95%CI:0.36-0.96) was associated with a lower risk for sleeping problems. Conclusion: Excessive infant crying and feeding problems may be related to interactional deficits of anxious mothers who perceive their infants as "difficult" during soothing or feeding situations. Sleeping problems may be transmitted already during pregnancy by an altered sleep-wake-rhythm of mothers with a history of depression or by a genetic predisposition. Therapeutic interventions should focus on maternal anxiety and depression, behavior management techniques to cope with difficult situations with "fussy" infants and potential protective factors (e.g. favorable maternal emotion regulation) to address crying, feeding and sleeping problems. Highlights: Strongest predictors for excessive crying and feeding problems were fussy infant temperament and maternal anxiety disorders. Maternal depressive disorders, single motherhood and cognitive reappraisal were associated with infant sleeping problem. Infant crying and feeding problems may be related to interactional problems of anxious mothers and their "difficult" infants. Sleeping problems may be transmitted genetically, physiologically or by altered sleep patterns of mothers with depression. Interventions should focus on maternal anxiety or depression and behavior management techniques to cope with regulatory problems.